Discussions on draft provisions on damages in the investor-state dispute settlement system in UNCITRAL Working Group III - José Manuel Álvarez Zárate (South Centre, 2024)
This paper summarizes the discussions within the United Nations Commission on International Trade Law (UNCITRAL) Working Group III (WG III) on the reform of investor-state dispute settlement (ISDS) regarding the two draft provisions on damages prepared by the UNCITRAL Secretariat as part of the two drafts on procedural and cross-cutting issues. It covers the period from September 2022 to July 8, 2024. It describes the draft provisions on damages and related provisions on procedural and cross-cutting issues of document A/CN.9/WG.III/WP.231, dated 26 July 2023, as well as the comments made on it by some members of WG III and observers. It also describes the changes to the above document contained in the second draft on the procedural and cross-cutting issues, dated July 8, 2024, contained in document A/CN.9/WG.III/WP.244. The purpose of this paper is to provide an overview of the comments made by some States on the draft provisions on damages, the substantive changes made by the Secretariat to the first draft, mostly based on the comments made by some States, and the exclusion of important aspects highlighted by some Global South States in their interventions. In the light of this review, countries of the Global South may consider commenting on document A/CN.9/WG.III/WP.244 to ensure that their concerns are effectively taken into account.
Keywords: 300; Damages; International Investment Agreements (IIAs); International Investment Regime; Investment; Investment Agreement; Investment Arbitration; Investor-State Dispute Settlement (ISDS) System; ISDS Reform; Procedural and Cross-cutting Issues; Reform of the IIA regime; UNCITRAL WGIII; United Nations Commission for International Trade Law (UNCITRAL)